Critical reflections on tourism: Phenomenological perspectives on global-South, degrowth and the role of visual aids - Lacerda-Nobre, Â.; Gameiro, A.; Duarte, R.; Jacquinet, M.; Pérez, R. (CIDADES, Comunidades e Territórios, 2023)
From a critical phenomenology perspective, it is possible to interpret tourism as an open arena where different players interact, thus illustrating the rationale behind their epistemic positioning. Tourism, as an economic sector, is both a product and a producer of what is happening at global level. This to-and-from mutual determinations may be exemplified by visual aids that help to map the conceptual models that shape scientific debate. The research objective of the present study is to critically explore the theoretical potential of the global-South paradigm in order to bring a better understanding of tourism, illuminating the creative tensions that are shaping this dynamic, complex, multifactorial and structuring sector. The global-South paradigm involves degrowth theories and other non-orthodox economic perspectives that determine how cities, communities and territories manage their symbolic and intangible heritage that, in turn, determine decision-making, political debate and, ultimately, the living conditions of their population. The contribution of the present research is to draw together a plethora of academic schools of thought that may help to critically identify the active forces in the tourism sector. The goal is not to offer detailed scientific evidence of the social, economic and political strains in tourism but to indicate and to highlight the potential that is already there to be explored in open reflection and in theoretical incursions, contributing to expand the horizons of thought and action of contemporary societies.